2016
DOI: 10.1371/journal.pone.0166687
|View full text |Cite
|
Sign up to set email alerts
|

Marathon Race Affects Neutrophil Surface Molecules: Role of Inflammatory Mediators

Abstract: The fatigue induced by marathon races was observed in terms of inflammatory and immunological outcomes. Neutrophil survival and activation are essential for inflammation resolution and contributes directly to the pathogenesis of many infectious and inflammatory conditions. The aim of this study was to investigate the effect of marathon races on surface molecules related to neutrophil adhesion and extrinsic apoptosis pathway and its association with inflammatory markers. We evaluated 23 trained male runners at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 39 publications
2
26
0
2
Order By: Relevance
“…As a matter of fact, IL-6 levels were found to be 0.51±0.26pg/mL in blood samples taken from twenty elite rowers (Jürimäe et al 2017). Similarly, the mean basal IL-6 level in 23 male marathoners was lower than 1 pg/mL and at the end of the marathon an increase of approximately 40 times was observed (Santos et al 2016). In other studies basal IL-6 levels were found to be 1.1±0,2pg/mL in 16 half marathoners (Nielsen et al 2016) and 0.54±0.07pg/mL in 9 male ultramarathon runners (Krzemiński et al 2016).…”
Section: R a F Tmentioning
confidence: 86%
“…As a matter of fact, IL-6 levels were found to be 0.51±0.26pg/mL in blood samples taken from twenty elite rowers (Jürimäe et al 2017). Similarly, the mean basal IL-6 level in 23 male marathoners was lower than 1 pg/mL and at the end of the marathon an increase of approximately 40 times was observed (Santos et al 2016). In other studies basal IL-6 levels were found to be 1.1±0,2pg/mL in 16 half marathoners (Nielsen et al 2016) and 0.54±0.07pg/mL in 9 male ultramarathon runners (Krzemiński et al 2016).…”
Section: R a F Tmentioning
confidence: 86%
“…Mountaineers have a more active lifestyle on a day-to-day basis than sedentary subjects which could have accounted for significantly higher mean CK in our study. Although CK values were found higher than in sedentary subjects they were within the mean baseline range for Caucasians 25,29 . AST and ALT are also expected to increase when CK is higher than normal 30 .…”
Section: Acute Phase Proteinsmentioning
confidence: 48%
“…Several authors report acute and chronic changes in immune system cells in practitioners of aerobic sports such as running, cycling, triathlon, and skating (Díaz et al, 2011;LaVoy et al, 2011;Brown et al, 2015;Santos et al, 2016;Barros et al, 2017;Koh and Park, 2018). The heterogeneity of the ways of estimating the intensity of interventions does not allow us to stipulate a better homogeneous pattern to be used.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term acute aerobic exercise with cycling, marathons, and triathlons lasting longer than multiple hours promotes elevations in plasma concentrations of IL-1ra, IL-6, IL-8, and IL-10 cytokines after exercise (Nieman et al, 2001;Ronsen et al, 2002;Suzuki, 2018). Leukocytes, neutrophils, interleukins 6, 10, 8, 12, tumor necrosis factor (TNF-α) and adhesion molecule (ICAM-1) have their plasma concentrations increased immediately after a 42.2 km marathon, enabling a post-exercise state of infection (Suzuki et al, 2003;Santos et al, 2016).…”
Section: Discussionmentioning
confidence: 99%